Validating candidate endpoints for intermediate age-related macular degeneration trials in a multi-centre setting: lessons from the MACUSTAR study - Terheyden, Jan H.; Dunbar, Hannah M. P.; Schmitz-Valckenberg, Steffen; Behning, Charlotte; Martinho, Cecília; Luhmann, Ulrich F. O.; Saßmannshausen, Marlene; Lüning, Anna; Miliu, Alexandra; Aires, Inês Dinis; Basile, Pier Giorgio; Batuca, Joana; et al. (Eye, 2025)
For the conduct of future interventional age-related macular degeneration (AMD) trials, the availability of clinical study endpoints is key. However, no endpoints have been accepted by regulators for evaluation of treatment for intermediate (i) AMD, i.e. the AMD stage at highest risk of developing irreversible geographic atrophy or macular neovascularization. The European MACUSTAR consortium has recruited more than 700 individuals to develop and validate structural, functional and patient-reported endpoints, enabling future iAMD trials based on a prospective observational, multi-centre cohort study. Reliably assessing candidate endpoints in a setting that involves multiple clinical sites across countries comes with a plurality of challenges in the study set-up, quality of data, recruitment of participants and study conduct. Therefore, the MACUSTAR consortium has established a framework that successfully addresses these topics, provides relevant insights into the natural history of iAMD and its sub-phenotypes, and will open new regulatory pathways. The MACUSTAR study is registered on ClinicalTrials.gov under NCT03349801.
Gesehen am 01.07.2025
Mitglieder des MACUSTAR CONSORTIUM: H. Agostini, I.D. Aires, L. Altay, R. Atia, F. Bandello, P.G. Basile, J. Batuca, C. Behning, M. Belmouhand, M. Berger, A. Binns, C.J.F. Boon, M. Böttger, J.E. Brazier, C. Carapezzi, J. Carlton, A. Carneiro, A. Charil, R. Coimbra, D. Cosette, M. Cozzi, D.P. Crabb, J. Cunha-Vaz, C. Dahlke, H. Dunbar, R.P. Finger, E. Fletcher, M. Gutfleisch, F. Hartgers, B. Higgins, J. Hildebrandt, E. Höck, R. Hogg, F.G. Holz, C.B. Hoyng, A. Kilani, J. Krätzschmar, L. Kühlewein, M. Larsen, S. Leal, Y.T.E. Lechanteur, D. Lu, U.F.O. Luhmann, A. Lüning, N. Manivannan, I. Marques, C. Martinho, A. Miliu, K.P. Moll, Z. Mulyukov, M. Paques, B. Parodi, M. Parravano, S. Penas, T. Peters, T. Peto, S. Priglinger, R. Ramamirtham, R. Ribeiro, D. Rowen, G.S. Rubin, J. Sahel, C. Sánchez, O. Sander, M. Saßmannshausen, M. Schmid, S. Schmitz-Valckenberg, J. Siedlecki, R. Silva, E. Souied, G. Staurenghi, J. Tavares, D.J. Taylor, J.H. Terheyden, A. Tufail, P. Valmaggia, M. Varano, A. Wolf and N. Zakaria